Effects of Different Interventions Using Taekwondo, Boxing, and Elastic Band Training on Body Composition and Physical Function in Chilean Older Women: A Randomized Controlled Trial - Edgar Vásquez-Carrasco; Jordan Hernandez-Martinez; Izham Cid-Calfucura; Eduardo Guzmán-Muñoz; Camila Ruiz; Camila Baeza; María José Márquez; Tomás Herrera-Valenzuela; Braulio Henrique Magnani Branco; Eduardo Carmine-Peña; Paulina Sepúlveda; Cristian Sandoval; et al. (Life)
Background: Interventions involving Olympic combat sports, such as Taekwondo (TKD) and Boxing (BOX), represent innovative approaches for promoting health in older people. Elastic bands training (EBT), by contrast, is a safe and cost-effective method that has demonstrated positive effects on functional physical parameters in this population. This study aimed to compare the effects of TKD and BOX interventions, relative to EBT, on body composition and physical function in Chilean older women. Methods: This randomized controlled trial comprised three parallel groups: TKD (n = 10), BOX (n = 10), and EBT (n = 10). Participants in each group underwent pre- and post-intervention assessments following two 60 min sessions per week over an eight-week period. Results: Multiple comparisons revealed significant advantages for EBT over TKD and BOX in maximal isometric handgrip strength for both the dominant (p < 0.001; d = 0.967, large effect) and non-dominant (p < 0.001; d = 0.641, moderate effect) hands. Conversely, significant improvements in Timed Up-and-Go performance were observed in the TKD and BOX groups compared to EBT (p < 0.001; d = 2.071, large effect). All groups showed significant within-group improvements in the 30 s chair stand test (p < 0.001; d = 0.095, large effect). No significant changes were found in body fat percentage, fat-free mass, back scratch test, sit-and-reach test, or 2 min step test across groups. Conclusions: Although no substantial differences were observed between groups for most variables, TKD and BOX interventions significantly reduced Timed Up-and-Go times, whereas EBT enhanced maximal isometric handgrip strength in both hands. These findings highlight the distinct functional benefits of each intervention modality for older Chilean women.